Urgensi Penerapan Doktrin Market Shared Liability di Indonesia pada Wilayah Aglomerasi Guna Mengatasi Unidentified Polluter - Rayi Kharisma Rajib; Moh Hikmal Adnan; Rafka Raditya Kurniawan (JURNAL ILMIAH NUSANTARA, 2026)
Environmental pollution in agglomeration areas creates challenges in environmental law enforcement because the source of pollution is often difficult to identify specifically (unidentified polluter). Conventional liability mechanisms that require proof of an individual causal relationship make it difficult for victims to obtain legal protection, even though environmental and public health damages are clearly evident. The Market Shared Liability (MSL) doctrine is considered relevant because it allows liability to be imposed proportionally based on the market share or contribution level of each corporation to the pollution. The implementation of this doctrine is important to overcome evidentiary deadlocks in collective pollution cases within agglomeration areas and to ensure the protection of the public’s right to a good and healthy environment. Therefore, explicit regulation regarding Market Shared Liability in Indonesia’s environmental procedural law is necessary. Keywords: Market Shared Liability, unidentified polluter, agglomeration areas, environmental law.   Abstrak. Pencemaran lingkungan di wilayah aglomerasi menimbulkan kesulitan dalam penegakan hukum karena sumber pencemar sering kali tidak dapat diidentifikasi secara spesifik (unidentified polluter). Mekanisme pertanggungjawaban konvensional yang mensyaratkan pembuktian hubungan kausal secara individual menyebabkan korban kesulitan memperoleh perlindungan hukum, meskipun kerugian lingkungan dan kesehatan masyarakat nyata terjadi. Doktrin Market Shared Liability (MSL) menjadi relevan diterapkan karena memungkinkan pembebanan tanggung jawab secara proporsional berdasarkan pangsa pasar atau tingkat kontribusi masing-masing korporasi terhadap pencemaran. Penerapan doktrin ini penting untuk mengatasi kebuntuan pembuktian dalam kasus pencemaran kolektif di wilayah aglomerasi serta menjamin perlindungan hak masyarakat atas lingkungan hidup yang baik dan sehat. Oleh karena itu, diperlukan pengaturan eksplisit mengenai Market Shared Liability dalam hukum acara lingkungan di Indonesia.